The Fontainhas Trilogy: bodies in transit, memories on the move - Zavaleta Silva, Cassandra (2025)
Pedro Costa’s Fontainhas Trilogy—Ossos (1997), No Quarto da Vanda (2000), and Juventude em Marcha (2006)—offers a unique approach to the experience of uprooting and exclusion in contemporary Lisbon. Through a minimalist and collaborative aesthetic, the filmmaker constructs a bodily archive that highlights the precariousness of the inhabitants of Fontainhas, a predominantly Cape Verdean migrant community. His approach avoids both exoticism and the aestheticization of suffering, placing bodies as active narrators of memories, struggles, and resistance.Each film articulates a specific dimension of this living archive: in Ossos, bodies embody the vulnerability of daily survival; in No Quarto da Vanda, confinement and addiction reveal the inscription of pain in the intimate; and in Juventude em Marcha, Ventura’s walk bears witness to the loss of territory and the persistence of collective memory in the face of gentrification. Taken together, the trilogy shows that displaced bodies are also political agents that challenge the viewer and reconfigure dominant narratives about poverty and migration. This analysis proposes reading Costa’s cinema as an exercise in visual anthropology that problematizes the representation of marginality and proposes an ethics of the gaze. His images remind us that bodies, even when expelled from spaces, resist as living archives capable of transforming memory and challenging oblivion.